Examining Teachers’ Readiness in the Implementation of the Merdeka Curriculum in Public Elementary Schools: A Case Study in Padangsidimpuan - Nursyaidah, Nursyaidah; Siregar, Fitri Rayani; Putri, Yulia Eka; Simbolon, Ali Mustopa Yakub; Safitri, Adek (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
Implementation of the Independent Curriculum set by the government raises a number of challenges in the field, especially those related to teacher and school readiness. This curriculum demands a comprehensive understanding from educators and school officials, especially at the elementary school level. This research uses a qualitative descriptive approach, with data collection through observation, interviews and document analysis. The data analysis process includes stages of reduction, presentation and drawing conclusions. The research results show that the readiness of teachers in Padangsidimpuan City public elementary schools in implementing the Independent Curriculum is at a fairly good level. This is reflected in the teacher's ability to understand the main components of the curriculum, including lesson planning, implementation of the teaching and learning process, and learning assessment. Teachers also demonstrate adequate understanding of learning tools, such as legal foundations, learning objectives, media, learning models, and supporting facilities and infrastructure. This readiness is supported by teachers' active participation in various professional development programs, such as training through the Merdeka Mengajar Platform (PMM), seminars, webinars, workshops and In House Training (IHT). Apart from that, teachers are able to develop open learning modules, implement differentiated learning in class, and carry out evaluations according to the Independent Curriculum guidelines.